Outcome of neck of femur fracture in elderly treated non operatively in Hospital Selayang - Appadurai, Shri Kapilan (2016)
INTRODUCTION: Femoral neck fracture is a common occurrence among the elderly age group especially when the aging population around the world is on the rise. This type of fracture poses a high mortality and morbidity, hence, they are commonly treated operatively to prevent complications. However, this fractures has been treated non-operatively in certain circumstances. In this study, we assess the functional outcome of elderly patients with femoral neck fracture that was treated non-operatively. METHODS: We recruited 55 patients in this study from January 2010 to January 2014. Out of the total 55 patients, the patients who are still alive are called and interviewed in the clinic. The functional outcome after neck of femur fracture being treated non-operatively were assessed using the SF-36 health survey questionnaire. The reason for opting non-operative treatment were explored and also the major cause of mortality among these patient was also identified. RESULTS: From our small series conducted, the survival rate for elderly patients with neck of femur fracture treated non-operatively was 58.2%. The mortality rate for elderly patients with neck of femur fractures treated non-operatively was around 41.8% per year. With regards to the quality of life, the functional assessment for our patients revealed that they fare fairly when the mental component is taken into account. With the mean Mental Component Summary (MCS) of 57.5 and mean Physical Component Summary (PCS) of 46.3.This means the functional outcome for elderly patients with neck of femur fracture treated non-operatively was average based on the Mental Component Summary (MCS) score and was below average for the Physical Component Summary (PCS) score. There were 2 reason identified for these patients opting for non-operative